Geodiversity and geoheritage in the perspective of geography - Claudino-Sales, Vanda (Bulletin of Geography. Physical Geography Series, 2021)
The paper states that geodiversity is the abiotic complement to biodiversity, and is considered to be the elements associated with the abiotic environment, e.g. geological diversity, geomorphodiversity, pedodiversity, hydrodiversity and climodiversity. Geoheritage is considered as the geological heritage of a site, but is here presented as the abiotic heritage of a site, and is related to geological heritage, geomorphoheritage, pedoheritage, hydroheritage and climoheritage. Thus, it is possible to talk about geological sites, geomorphosites, pedosites, hydrosites and climosites. Geodiversity and geoheritage are strongly linked to geology. However, it is also a new paradigm to geography, as physical geography classically works with abiotic and biotic environments.